Family psychoeducation for serious mental illness - Lefley, Harriet P. (New York ; Oxford : Oxford University Press, 2009)
Research shows that many American adults with serious mental illness live with or maintain contact with their families; but families are rarely given information about their relative's illness & their own needs for support are ignored. Harriet Lefley traces the history of family psychoeducation in the U.S.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Mental illness -- Treatment; Family psychotherapy; Evidence-based psychiatry